Hybrid Contract Dalam Transaksi Syariah Perspektif Maqashid Syariah - Setiawan, Setiawan (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The complexity of modern economic problems today also demands flexibility in offering solutions to the problems faced. This has led to various Islamic banking businesses that were previously unknown but are now growing. Among the main points in creating Islamic banking and financial products to meet the needs of modern society is the development of Hybrid Contract. The main problem in this research is how maqashid sharia views the implementation of hybrid contracts in Islamic banking amidst the debate between scholars who are pro and contra. This research method uses a qualitative approach. Hybrid contracts or multi-contracts are addressed differently by scholars, but in contemporary business, especially Islamic banking, hybrid contracts are allowed on condition that they are carried out individually and not simultaneously. Hybrid Contract in the concept of maqāsid al-sharī'ah is a combination of contracts applied to many Sharia Financial Institutions as an effort to achieve contemporary business flexibility, make it easier for people to meet their needs, and efforts to achieve multidimensionality. The existence of Hybrid Contract is needed to meet the needs of transactions in this modern era. This is because sharia financial/business products experience very dynamic developments and "force" financial institutions to continue to follow the development of modern transaction models.